Taxonomic studies on Zingiber (Zingiberaceae) in China IV: Z. pauciflorum sp. nov. from Yunnan. (30th March 2018) - Bai, Lin; Leong‐Škorničková, Jana; Li, Dezhu; Xia, Nianhe
Abstract : Zingiber pauciflorum L.Bai, Škorničk., D.Z.Li & N.H.Xia (Zingibereae, Zingiberaceae), a new species from southern Yunnan, China, is described and colour plates are provided. It belongs to Z . sect. Cryptanthium Horan. and is compared with three similar species, namely Z. tenuifolium L.Bai, Škorničk. & N.H.Xia, Z. smilesianum Craib and Z. yunnanense S.Q.Tong & X.Z.Liu. A colour plate of the most similar species, Z. smilesianum is also provided for comparison.